Transvenous Extraction and Removal of Pacing Leads Placed after Cardiac Transplantation - Caleb Norton; Benjamin Holmes; Asad Al Aboud; Eun-Jeong Kim; Holly Gonzales; Christopher Ellis; Roy John; George H. Crossley; Jay Montgomery (Case Reports in Cardiology)
There is an increasing prevalence of cardiac implantable electronic devices (CIEDs) due to expanding adoption and availability of these evidence-based therapies. With the increased prevalence of these life-saving devices, there has also been an increased demand for lead removal and lead extraction. Understanding the specific subgroups of patients at high risk for complications during and after lead extraction has become imperative to properly manage endovascular CIED leads. There have been multiple published studies describing clinical variables that predict adverse outcomes in CIED system extractions; however, the risk of complications in leads placed after cardiac transplantation has not specifically been addressed to date. We present four cases of transvenous extraction and removal of pacing leads placed after cardiac transplantation. There were no major complications related to extraction in these four cases; however, three of the four patients died within one year after the procedure. While the etiology of death in these cases seemed to be unrelated to the extraction procedure, the indications for extraction (infection in the setting of immunosuppression and calcineurin-associated ESRD and poor sensing/capture possibly secondary to chronic rejection and/or frequent right heart biopsies) likely contributed at least indirectly to the subsequent death.